Le bourgeois gentilhomme : comédie-ballet. Nouvelle ed. classique, avee une notice préliminaire et des notes d'après la grande éd. faisant partie des Chefs-d'oeuvre de la littérature francaise / par L. Moland. - Molière, 1622-1673. (Tufts University. Tisch Library., 2016)
1 online resource (2 preliminary leaves, 142 pages, 1 leaf); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.